The Origins of the Fantastic in Horace Walpole’s Prefaces to The Castle of Otranto - Olivé, Laia (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2023)
Widely considered the first Gothic novel, The Castle of Otranto (1764) is twice prefaced by an author who is aware of the risks he was taking in challenging the contemporary literary canon. Both texts lay out some of the Gothic particularities found not only in subsequent narratives of this kind, but also in fantastic tales, which will appear half a century later. The aim of this article is to track the origins of the fantastic in Horace Walpole’s prefaces so as to understand it better and discuss its development and divergence from the Gothic. Theories on the Gothic novel and the fantastic are also examined.